2015
DOI: 10.15835/nbha4319586
|View full text |Cite
|
Sign up to set email alerts
|

Total Antioxidant Capacity and Total Phenolics Content of <i>Phyllostachys</i> Taxa Shoots

Abstract: Total phenolic content (TP) and total antioxidant capacity (AC) were analysed in shoots of Phyllostachys aureosulcata (PA), P aureosulcata f. aureocaulis (PAA), P. aureosulcata f. spectabilis (PAS), P. bissetii (PB), P. flexuosa (PF), P. humilis (PH), P. iridescens (PI), P. nigra var. nigra (PNN), P. nigra var. henonis (PNH), P. mannii (PM), P. sulphurea var. sulphurea (PSS), P. violascens (PVI), P. viridiglaucescens (PVG), P. vivax f. aureocaulis (PVA), collected on four harvest dates. Both TP and AC were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…It is observed that the antioxidant activity of an EO is dependent upon the plant and/or parts used to produce the oil [42]. The antioxidant activities of BEO can be directly correlated to its total phenolics content as reported by researchers for other essential oils [43,44]. The total phenolics and flavonoid contents are the two key indicators widely employed to represent the overall antioxidant activity in the samples.…”
Section: Total Phenolics Flavonoids and Fatty Acids Content Of Beomentioning
confidence: 94%
“…It is observed that the antioxidant activity of an EO is dependent upon the plant and/or parts used to produce the oil [42]. The antioxidant activities of BEO can be directly correlated to its total phenolics content as reported by researchers for other essential oils [43,44]. The total phenolics and flavonoid contents are the two key indicators widely employed to represent the overall antioxidant activity in the samples.…”
Section: Total Phenolics Flavonoids and Fatty Acids Content Of Beomentioning
confidence: 94%
“…Total phenolic content (TPC) was measured by the Folin-Ciocalteu method ( 31 ). Briefly, extractions were performed in darkness for 30 min with ethanol (80% v/v) in an ultrasonic bath.…”
Section: Methodsmentioning
confidence: 99%
“…In the 1990's Ishii and Hiroi (1990) invented a Diferuloyl arabinoxylan Compound, the compound that contains 5-5 linkage diferuloyl isolated from bamboo shoots and is named as a ferulic acid [9]. Some studies show Dendrocalamus, Bambusa, Phyllostachys species having more antioxidant properties in their shoots [10,11].…”
Section: Antioxident Propertiesmentioning
confidence: 99%